CULTIVATING OF AN URBAN ENVIRONMENT OF CHANGES - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2024)
The population of cities (especially large metropolitan areas) is an indicator, a “litmus test”, and a catalyst for global transformations. Often, the opinions and assessments of city residents can be used to judge the preparation and growth of certain changes in the country's views [1-5]. Such recording is even more accurate when significant alterations of paradigmatic scale and depth are maturing.